2008
DOI: 10.1088/1468-6996/9/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

A new route for preparation of sodium-silicate-based hydrophobic silica aerogels via ambient-pressure drying

Abstract: An in-depth investigation into the synthesis of hydrophobic silica aerogels prepared by the surface derivatization of wet gels followed by subsequent drying at ambient pressure is reported. The following sol-gel parameters were examined for their effect on the physical properties of the derived aerogels: number of gel washings with water, percentage of hexane or methanol in silylating mixture, molar ratio of tartaric acid: Na 2 SiO 3 , gel aging period, weight% of silica, trimethylchlorosilane (TMCS) percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 31 publications
0
17
0
3
Order By: Relevance
“…The efficiency of deionised water washings to free the gel from sodium sulphate was monitored by atomic absorption spectroscopy (AAS) analysis of the silicas obtained after drying. The result indicated that Na + decreased from 36.5% (on the basis of stoichiometry) [25] to 1.6% in the SS-based silica and to 2.1% in the CS based silica.…”
Section: Hydrolysis and Gelationmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of deionised water washings to free the gel from sodium sulphate was monitored by atomic absorption spectroscopy (AAS) analysis of the silicas obtained after drying. The result indicated that Na + decreased from 36.5% (on the basis of stoichiometry) [25] to 1.6% in the SS-based silica and to 2.1% in the CS based silica.…”
Section: Hydrolysis and Gelationmentioning
confidence: 99%
“…The water glass obtained from the basic reaction is similarly hydrolysed to silicic acid which undergoes condensation to disilicic acid and further reaction to a polycondensed hydrogel [24] as shown in Scheme 1. Thereafter, the gel obtained from both precursor compounds were subjected to multiple washings [25] with deionised water to free the gel of sodium sulphate formed during hydrolysis that is trapped in the pores of the gel network. During aging, the 3-D framework of the silicate glass continues to grow and becomes more rigid by contracting and expelling liquid water present inside the pores [26].…”
Section: Hydrolysis and Gelationmentioning
confidence: 99%
“…after thermal shock. Pore size of hydrophilic aerogel become larger and the number of pores decreased in the same volume [14]. It suggests that part of pore was collapsed, which increase the surrounding space.…”
Section: Microstructure Evolution During the Shock Processesmentioning
confidence: 98%
“…Therefore, the APD method is a more economical process compared to the SCD method and is able to operate continuously as opposed to producing batches [ 17 ]. Hexane is a well-known low-surface-tension solvent and it has been often used in the APD synthesis of silica aerogels [ 18 20 , 23 ]. In this work, we also choose hexane as drying solvent because solvent combination of methanol and hexane has been previously reported in solvent exchange for aerogel preparation [ 23 ], and study different phases of porous Zn-based/ZnO composites by APD method of synthesis.…”
Section: Introductionmentioning
confidence: 99%